Performance of the 4th Scientific Olympiad of Medical Students of the Universities of Medical Sciences in Iran about Empowerment and Loyalty - Seiyed Davoud Nasrollahpour Shirvani; Mostafa Javanian; Ali Shabestani Monfared; Iman Jahanian (Kerman University of Medical Sciences, 2014)
Background & Objective: Scientific Olympiads are planned to identify creative innovative and the most talented students These competitions create cheerful environments in order to increase the capabilities and motivation of the students Satisfaction and loyalty of the participants are suitable characteristics to evaluate the efficacy of an Olympiad This study was performed to evaluate the success rate of the 4th Scientific Olympiad of Medical Students of Iran about empowerment and loyalty in the participants viewpoints   Methods: This crosssectional study was conducted in 201213 on the participants of the 4th Medolympiad of Iran The research sample was selected by census Data collection was performed by a researchermade questionnaire the validity and reliability of which were confirmed The data were analyzed using SPSS software at significant level of < 005   Results: Among the 320 participants from 4 groups 62 students (27%) were in the domain of basic science 50 students (22%) in clinical reasoning 56 students (24%) in health management and 61 students (27%) in innovation The mean score of preparation in the Universities of Medical Sciences was 25 ± 11 (out of the total score of 5) The 4th Medolympiad gained a score of 32 ± 11 out of 5 in personal empowerment and 37 ± 12 out of 5 in loyalty There was a significant correlation between the level of preparation in Medical Universities and the type of university (P < 0001) There was a significant correlation between the level of loyalty and the type of university (P < 0001) Moreover there was a significant correlation between the level of loyalty and academic degree of students (P = 0029)   Conclusion: The success rate of the 4th Medolympiad in terms of empowerment and loyalty of students was higher than the moderate level therefore it is necessary to improve the subsequent periods